Implementación de un prototipo para la clasificación y el monitoreo de fallas de cercas eléctricas ganaderas usando Machine Learning (2022)
The use of electric fences is of vital importance for the agricultural sector worldwide, as they provide security and protection to crops, animals and properties. Its operation is of constant use with exposure to climatic changes, these factors in the long term cause inefficiency in the fence, therefore, it is of utmost importance to analyze and monitor its performance.